Insights for Egypt's and Tunisia's Islamists from Turkish experience of democratic transition - (:unkn) unknown (My University, 2013)
Turkey is achieved a viable combination of Islam, democracy and development. After prolonged periods of political instability and interruptions in democratic rule, the Islamic-leaning AK Party government overcame the hurdles preventing it from reaching power in the early 2000s. It achieved a significant degree of democratization and economic growth without oil or foreign aid and repeatedly won elections ever since. As such, the party's success offers important lessons for Islamists in Tunisia, Egypt and Morocco. The lessons of the Turkish experience are especially relevant in dealing with the opposition and democratization, as well as achieving stability and growth.